Rainwater harvesting in Dry Chaco: Regional distribution and local water balance - Magliano, Patricio Nicolás (2015)
Rainwater harvesting (RWH) has been essential for the establishment of human settlements in many dry regions of the world that lacked suitable surface or groundwater resources. A vast fraction of the South American Dry Chaco ecoregion still relies on RWH to support, not only livestock production, but domestic and industrial uses as well. As a result, water capture and storage infrastructure is widely disseminated throughout the region. In this paper we characterized the most typical RWH systems in two contrastingly developed sub-regions of Dry Chaco, ranging from extensive ranching to intensive beef and dairy production (central Argentina and western Paraguay, respectively). In each sub-region, we quantified RWH systems density, spatial distribution and associations with landscape features; furthermore, we illustrated how the daily dynamic of water stock in a typical RWH system contributes to assess their capture and storage efficiency. We found that randomly distributed low sophisticated RWH systems prevailed in central Argentina, while clustered distributed high sophisticated ones were more common in western Paraguay. RWH systems density was ten times higher in western Paraguay (0.94 vs. 0.098 units/km2), showing an exponential association with land cleared fraction and proximity to villages. The daily dynamic of water stock of the RWH impoundment showed that water harvest events were exponentially associated with precipitation magnitude events (R2 = 0.86), while annual water losses were explained by infiltration and evaporation fluxes (59 vs. 41%, respectively). Across both sub-regions, RWH accounts for less than 1% of the annual precipitation, playing a minor role on the regional water balance; however at a local level, they can affect several hydrological fluxes including the onset of groundwater recharge and the mitigation of extreme runoff events.